Understanding the Adoption of Green Technologies by Indonesian Micro and Small Enterprises: A Qualitative Study on Triple Bottom Line Practices - Yeldy Dwi Genadi; Adrianda Anwar (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2026)
Micro and small enterprises (MSEs) dominate Indonesia's business population, yet their transition toward environmentally responsible production remains uneven because sustainability decisions are made under severe resource, capability, and market constraints. This study investigates how Indonesian MSE owners perceive, adopt, and operationalize green technologies and how these practices are translated into triple bottom line outcomes. An exploratory qualitative design was applied through semi-structured interviews with 12 MSE owners in food processing, handicraft, and retail-related sectors in Mataram and surrounding Lombok districts. Field observations and business documents were used for triangulation, and thematic analysis was conducted to identify adoption drivers, barriers, stakeholder support mechanisms, and perceived sustainability outcomes. The findings show that green technology adoption is primarily triggered by cost reduction, market differentiation, customer pressure, and external facilitation, while adoption is constrained by upfront investment, maintenance uncertainty, weak technical knowledge, and fragmented policy support. Although adoption remains incremental, it contributes to profit through lower operating costs, to people through safer and more skill-intensive work routines, and to planet through waste reduction and more efficient resource use. The study extends green innovation and sustainable entrepreneurship literature by showing how resource-constrained MSEs build informal but meaningful sustainability pathways through stakeholder-supported, practice-based adoption.